Desempenho de uma escala analógica visual legendada na determinação do grau de dispneia durante teste de broncoespasmo induzido por exercício em crianças e adolescentes asmáticos - Lima, Patrícia Bueno [UNIFESP] (2010)
OBJECTIVE: There is an indirect relationship between airway obstruction in asthma and the intensity of breathlessness (dyspnea). A word labeled visual analog dyspnea scale with a 0-3 score has been widely used for the assessment of the degree of bronchoconstriction, although the perception of such obstruction varies considerably. The objective of this study was to determine whether children and adolescents are able to perceive acute exercise-induced bronchoconstriction (EIB), as well as to measure the discriminatory power of a word labeled visual analog dyspnea scale in relation to the intensity of the EIB. METHODS: A cross-sectional study involving 134 children and adolescents with asthma and submitted to a six-minute steady-state exercise test on a cycle ergometer. The intensity of dyspnea was determined using a word labeled visual analog dyspnea scale prior to each determination of FEV1. The scale is scored from 0 to 3, with a logical sequence of pictures, ranging from no symptoms to severe dyspnea. Variables were determined at baseline, as well as at 5, 10, and 20 min after the exercise test. The accuracy of the dyspnea scale in identifying the degree of EIB was determined by means of ROC curves for the post-exercise fall in FEV1, using cut-off points of 10%, 20%, 30%, and 40%. RESULTS: Of the patients selected, 111 finished the study, and 52 (46.8%) presented with EIB. The area under the ROC curve increased in direct proportion to increases in the degree of bronchoconstriction. CONCLUSIONS: Among children and adolescents with asthma, the accuracy of this dyspnea scale improves as the post-exercise percentage fall in FEV1 increases. However, the predictive value of the scale is suboptimal when the percentage fall in FEV1 is lower.